1988
DOI: 10.1902/jop.1988.59.9.557
|View full text |Cite
|
Sign up to set email alerts
|

Use of Antimicrobial Containing Acrylic Strips in the Treatment of Chronic Periodontal Disease

Abstract: Local antimicrobial therapy has been considered for use in the treatment of chronic periodontal disease. This study evaluated chlorhexidine, metronidazole, and tetracycline delivered into periodontal pockets in an acrylic resin vehicle and compared the results with root planed and untreated sites over a three-month follow-up period. One site per patient where pocketing greater than or equal to 6 mm associated with a single rooted tooth was randomly allocated to one of the five possible regimens. Baseline and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 28 publications
(3 reference statements)
2
24
0
1
Order By: Relevance
“…However, when a thin ethylcellulose film containing 20% metronidazole was placed in the pockets, it too was ejected and needed to be anchored to the tooth with a dollop of glass-ionomer cement (Loesche et al, 1996). Likewise, acrylic films containing various antimicrobial agents had to be secured with a periodontal dressing (Addy et al, 1988). In practice, then, non-biodegradable delivery systems need some type of retention mechanism to keep them in place.…”
Section: (D) Diagnosis Of An Anaerobic Infectionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, when a thin ethylcellulose film containing 20% metronidazole was placed in the pockets, it too was ejected and needed to be anchored to the tooth with a dollop of glass-ionomer cement (Loesche et al, 1996). Likewise, acrylic films containing various antimicrobial agents had to be secured with a periodontal dressing (Addy et al, 1988). In practice, then, non-biodegradable delivery systems need some type of retention mechanism to keep them in place.…”
Section: (D) Diagnosis Of An Anaerobic Infectionmentioning
confidence: 99%
“…However, it may be that the differences observed are really due to characteristics of the vehicle, which determines the bioavailability of agents such as chlorhexidine. Thus, the apparent ineffectiveness of chlorhexidine in the acrylic strips (Addy et al, 1988) should not be compared with its apparent effectiveness in the biodegradable delivery system For a systemic agent to be effective, it has to be efficiently absorbed in the intestines, circulate in the vascular system to penetrate the extravascular space, and enter the pocket via the gingival crevicular fluid. If the GCF flow is about 20 jLL/hr (Goodson, 1994), this means that, in a 6-mm pocket, about 480 [iL of GCF containing from 1 to 5 pg of the agent arrives per day to do battle with the 100,000,000 bacteria that are adhering to the tooth.…”
Section: (D) Diagnosis Of An Anaerobic Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addy et al (1982) described formulations which delivered, in vitro, therapeutic levels of all three drugs over a 14-day period. In later studies (Yeung et al, 1983;Addy and Langeroudi, 1984;Addy et al, 1988), they showed various degrees of clinical efficacy, but this system has not been developed for clinical use.…”
Section: Types Of Devices Thatmentioning
confidence: 99%
“…These delivery systems can locally provide inhibitory concentrations toward the periodontal pathogens of the drug for several days. Periodontal fibers, [4] strips, [5] and gels [6] were already studied.…”
Section: Introductionmentioning
confidence: 99%